PERTUMBUHAN DAN HASIL PAKCOY (Brassica rapa L.) TERHADAP PEMBERIAN BIOCHAR TEMPURUNG KELAPA PADA TANAH GAMBUT PEDALAMAN: Application of Coconut Shell Biochar for Increasing The Growth and Yield of Pakcoy (Brassica rapa L.) on Peat Land - Abdul Hamid, Syahrudin; Syahid, Abdul; Dewi Sihite, Irene; Adji, Fengky F; Asie, Kambang Vetranie (Fakultas Pertanian Universitas Palangka Raya, 2023)
The purpose of this experiment was to study the growth and yield of pakcoy (Brassica rapa L.) the giving of coconut shell biochar on peat land. This research was conducted from June to August 2022. This research was conducted in a plastic house located on Jl. Haka, Panarung Village, Pahandut District, Central Kalimantan. This study used Randomized Compete Design (RCD) of single factor that was coconut shell biochar consisting of 5 levels of treatment namely B0 (0 ton ha-1), B1 (4 ton ha-1), B2 (6 ton ha-1), B3 (8 ton ha-1), and B4 (10 ton ha-1). The results showed that the application of coconut shell biochar had a significant effect on the growth and yield of pakcoy plants on peat land. Application coconut shell biochar dose of B4 = 10 ton ha-1 (113.6 g. polybag-1) was the best treatment for the growth and yield of pakcoy plants on peat land with an average plant fresh weight of 91.92 g-1.